2012
DOI: 10.2215/cjn.11311111
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin, Copeptin, and Renal Concentrating Capacity in Patients with Autosomal Dominant Polycystic Kidney Disease without Renal Impairment

Abstract: SummaryBackground and objectives Autosomal dominant polycystic kidney disease (ADPKD) is the most prevalent hereditary renal disease, characterized by cyst formation in the kidneys leading to end stage kidney failure. It is clinically acknowledged that ADPKD patients have impaired urine concentrating capacity, but the mechanism behind this observation is unknown.Design, setting, participants, & measurements Fifteen ADPKD patients (estimated GFR $60 ml/min per 1.73 m 2 ) and 15 age-and sex-matched healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 37 publications
4
84
1
1
Order By: Relevance
“…15 In ADPKD, however, it is important to distinguish an early and rather mild urinary concentration deficit from the severe urinary concentration deficit associated with many forms of ESRD in the late course of the disease. In fact, as shown by Zittema et al 11 and Gabow et al 16 in large patient cohorts, maximal urine concentration capacities (maximal urine osmolality after overnight thirsting) are reduced but remain well above serum osmolality. In addition, Zittema et al 11 showed that patients carrying a polycystic kidney disease 1 (PKD1) mutation have early urine concentration deficits and increased vasopressin/copeptin levels.…”
Section: Pathophysiology Of Osmoregulation In Adpkdmentioning
confidence: 87%
See 1 more Smart Citation
“…15 In ADPKD, however, it is important to distinguish an early and rather mild urinary concentration deficit from the severe urinary concentration deficit associated with many forms of ESRD in the late course of the disease. In fact, as shown by Zittema et al 11 and Gabow et al 16 in large patient cohorts, maximal urine concentration capacities (maximal urine osmolality after overnight thirsting) are reduced but remain well above serum osmolality. In addition, Zittema et al 11 showed that patients carrying a polycystic kidney disease 1 (PKD1) mutation have early urine concentration deficits and increased vasopressin/copeptin levels.…”
Section: Pathophysiology Of Osmoregulation In Adpkdmentioning
confidence: 87%
“…[8][9][10][11] One key advance in the past 5 years was the development of more robust and reliable assays to measure and estimate concentration of vasopressin in the serum. 12 Copeptin, a 39-amino acid glycopeptide comprising the C terminus of the vasopressin precursor (preprovasopressin), is cosecreted with vasopressin by the neurohypophysis, which is somewhat comparable with cosecretion of the C peptide and insulin by the pancreas.…”
Section: Pathophysiology Of Osmoregulation In Adpkdmentioning
confidence: 99%
“…10 Besides the above-mentioned pathological observations, large-scale retrospective studies suggested a high-level plasma copeptin (a surrogate of vasopressin), is associated with the progression of kidney diseases. [11][12][13][14][15] For example, positive associations were found between copeptin levels with disease severity in autosomal dominant polycystic kidney disease (ADPKD) patients. [11][12][13][14] Higher serum level of copeptin was also detected in kidney transplant recipients who have accelerated renal function decline.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] For example, positive associations were found between copeptin levels with disease severity in autosomal dominant polycystic kidney disease (ADPKD) patients. [11][12][13][14] Higher serum level of copeptin was also detected in kidney transplant recipients who have accelerated renal function decline. 12 From currently available literatures, it is clear that vasopressin (VP) regulates water reabsorption by a®ecting cellular distribution of a water channel protein aquaporin 2 in kidney epithelial cells; 7,[16][17][18] however, whether VP a®ects other cellular proteins that are responsible for maintaining cell polarity of kidney tubules, and as a consequence, contributes to the kidney diseases progression is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This "concentrating defect" can be detected in some young children and young adults decades before the GFR noticeably declines, indicating that parenchymal malfunction begins very early in the course of renal cystic disease (2). In an excellent study reported in this issue of CJASN, Zittema et al (3) confirm that maximal urine concentration capacity is lost in ADPKD patients compared with normal controls. Still at issue is the mechanism(s) by which ADPKD impairs the maximal concentration of the urine.…”
mentioning
confidence: 96%